Treatment Practices and Outcomes After Blunt Cerebrovascular Injury in Children. Issue 6 (25th July 2016) - Dewan, Michael C.; Ravindra, Vijay M.; Gannon, Stephen; Prather, Colin T.; Yang, George L.; Jordan, Lori C.; Limbrick, David; Jea, Andrew; Riva-Cambrin, Jay; Naftel, Robert P.
Abstract: BACKGROUND: Pediatric blunt cerebrovascular injury (BCVI) lacks accepted treatment algorithms, and postinjury outcomes are ill defined. OBJECTIVE: To compare treatment practices among pediatric trauma centers and to describe outcomes for available treatment modalities. METHODS: Clinical and radiographic data were collected from a patient cohort with BCVI between 2003 and 2013 at 4 academic pediatric trauma centers. RESULTS: Among 645 pediatric patients evaluated with computed tomography angiography for BCVI, 57 vascular injuries (82% carotid artery, 18% vertebral artery) were diagnosed in 52 patients. Grade I (58%) and II (23%) injuries accounted for most lesions. Severe intracranial or intra-abdominal hemorrhage precluded antithrombotic therapy in 10 patients. Among the remaining patients, primary therapy was an antiplatelet agent in 14 (33%), anticoagulation in 8 (19%), endovascular intervention in 3 (7%), open surgery in 1 (2%), and no treatment in 16 (38%). Among 27 eligible grade I injuries, 16 (59%) were not treated, and the choice to not treat varied significantly among centers ( P < .001). There were no complications from medical management. Glasgow Coma Scale (GCS) score <8 and increasing injury grade were predictors of injury progression ( P = .001 and .004, respectively). Poor GCS score ( P = .02), increasing injury grade ( P = .03), and concomitant intracranial injury ( P = .02) correlated with increased risk of mortality. Treatment modality did not correlate with progression of vascular injury or mortality. CONCLUSION: Treatment of BCVI with antiplatelet or anticoagulant therapy is safe and may confer modest benefit. Nonmodifiable factors, including presenting GCS score, vascular injury grade, and additional intracranial injury, remain the most important predictors of poor outcome.